1998
DOI: 10.1159/000013806
|View full text |Cite
|
Sign up to set email alerts
|

Basal Cochlear Lesions Result in Increased Amplitude of Otoacoustic Emissions

Abstract: We have measured the changes in transient otoacoustic emissions (TEOAEs) and distortion product otoacoustic emissions (DPOAEs) during and after ototoxic amikacin treatment in an animal (chinchilla) model. TEOAE and DPOAE were recorded from 6 adult chinchillas over a 6-week time course starting just before a 5-day or 7-day treatment period with amikacin sulphate (400 mg/kg/day, i.m.). After final recordings, cochlear morphology was assessed by scanning electron microscopy. Generally, both DPOAE and TEOAE amplit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
18
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 17 publications
9
18
0
Order By: Relevance
“…In addition, Konrad-Martin et al (2012b) reported that DPOAE enhancements were most common at frequencies below the damaged region identified by pure-tone hearing changes among Veterans exposed to cisplatin. Enhancement below the "audiometric edge" of the presumed damage is consistent with animal models of noise (Harding and Bohne 2004) and ototoxic exposures (Kakigi et al 1998;Mei et al 2009). Researchers have hypothesized that reduced activity of the medial olivocochlear system and/or removal of contributions from additional "basal sources" may play a role in generating enhancements in this context (Kakigi et al;Martin et al 2011).…”
Section: Va Author Manuscriptsupporting
confidence: 70%
See 1 more Smart Citation
“…In addition, Konrad-Martin et al (2012b) reported that DPOAE enhancements were most common at frequencies below the damaged region identified by pure-tone hearing changes among Veterans exposed to cisplatin. Enhancement below the "audiometric edge" of the presumed damage is consistent with animal models of noise (Harding and Bohne 2004) and ototoxic exposures (Kakigi et al 1998;Mei et al 2009). Researchers have hypothesized that reduced activity of the medial olivocochlear system and/or removal of contributions from additional "basal sources" may play a role in generating enhancements in this context (Kakigi et al;Martin et al 2011).…”
Section: Va Author Manuscriptsupporting
confidence: 70%
“…Enhancement below the "audiometric edge" of the presumed damage is consistent with animal models of noise (Harding and Bohne 2004) and ototoxic exposures (Kakigi et al 1998;Mei et al 2009). Researchers have hypothesized that reduced activity of the medial olivocochlear system and/or removal of contributions from additional "basal sources" may play a role in generating enhancements in this context (Kakigi et al;Martin et al 2011). In addition, DPOAEs are thought to arise from at least two generator mechanisms, nonlinear distortion and linear reflection, which interact constructively or destructively depending on their phase relationship (Shera & Guinan 1999).…”
Section: Va Author Manuscriptsupporting
confidence: 70%
“…Their most interesting observation was increased OAE amplitudes at frequencies basal to the lesioned frequency areas. Kakigi et al (1998) measured hearing status in chinchillas with DPOAEs and TEOAEs before, during, and after amikacin treatment. Kakigi et al (1998) found that when the basal most hair cells of the cochlea were damaged, OAE amplitudes increased particularly for stimulus frequencies bordering the damaged tonotopic region.…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that inflammatory process(es) somehow affect the mechanics of the basilar membrane and/or organ of Corti. Kakigi et al (1998) suggested that the site of lesion basal to the area being monitored might be responsible whereby the increased OAE amplitude is a "result of a more effective basal transmission signal across a less active, and therefore less interfering cochlear region" (p. 371). This speculation is not consistent with the significant interaction of frequency by group; namely that both groups of children with SCD showed similar increased DPOAE amplitudes in the lower frequencies (i.e., f 2 < 1546 Hz).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation